Residual Obstruction After Repair of Total Anomalous Pulmonary Venous Connection: Role of Perioperative Echocardiography. Issue 6 (15th March 2019) - Pillai, Manjusha N.; Gadhinglajkar, Shrinivas; Menon, Sabarinath; Sreedhar, Rupa
Abstract : Supplemental Digital Content is available in the text.